Structure of the Drosophila ALKA chloride channel responsible for alkaline taste sensation - Xiao, Jiaxian; Jia, Yu; Gong, Mingyu; Li, Yuqi; Li, Weiping; Qian, Dandan; Sun, Huahua; Yan, Renhong; Gong, Deshun (浪淘沙预印本平台, 2026)
The ALKA channel, a member of the Cys-loop ligand-gated ion channel (cysLGIC) family, has recently been identified as a receptor mediating alkaline taste sensation in Drosophila. However, the structure and molecular mechanism underlying pH sensing of ALKA channel remain to be determined. Here, we report the cryo-EM structure of ALKA, determined at a resolution of 2.86 Å under its physiological pH condition. ALKA forms a symmetric pentamer featuring a V-shaped pore architecture with a progressive constriction-to-expansion profile extending from its intracellular base toward the extracellular side. The primary constriction site is composed of five P276 residues, forming a narrow gate with a pore radius of approximately 1.6 Å-consistent with a closed state. The secondary constriction site, formed by five T280 residues (T280 ring), exhibits a similar pore radius of approximately 1.7 Å. At this site, a putative chloride ion is anchored through cooperative interactions involving both the T280 and T284 rings. Structural mapping reveals that five lysine residues may be involved in pH sensing, with K229 likely serving as the principal sensor owing to its strategic position in loop C. This structure serves as an important basis for understanding the functional mechanisms of the ALKA channel.